2021
DOI: 10.3390/membranes11080640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing Conditions and Plasticizing-Reinforcing Modification on the Crystallization and Physical Properties of PLA Films

Abstract: The polylactic acid (PLA) resin Ingeo 4032D was selected as the research object. Epoxy soybean oil (ESO) and zeolite (3A molecular sieve) were used as plasticizer and reinforcing filler, respectively, for PLA blend modification. The mixture was granulated in an extruder and then blown to obtain films under different conditions to determine the optimum processing temperatures and screw rotation. Then, the thermal behaviour, crystallinity, optical transparency, micro phase structure and physical properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…where: ∆H m is the melting enthalpy of PLA and BioPE; ∆H cc is the cold crystallization enthalpy; ∆H o is equilibrium melting enthalpy, where 100% crystalline PLA is 93.7 J/g [29], and 100% crystalline BioPE is 290 J/g [30]; W is the matrix content.…”
Section: Characterizationsmentioning
confidence: 99%
“…where: ∆H m is the melting enthalpy of PLA and BioPE; ∆H cc is the cold crystallization enthalpy; ∆H o is equilibrium melting enthalpy, where 100% crystalline PLA is 93.7 J/g [29], and 100% crystalline BioPE is 290 J/g [30]; W is the matrix content.…”
Section: Characterizationsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) analysis was performed on 5 g samples in a DSC‐Q20 (TA Instruments, New Castle, United States) in a temperature range of 25–200 °C, with second heating in a nitrogen atmosphere using a heating rate of 10°C/min and a gas flow rate of 50 ml/min. The degree of crystallinity (X c ) of the compounds was calculated according to Equation (2) [ 21 ] : Xc%=HmWxHmox100 where ∆ H m is the melting enthalpy of PLA and EVA, ∆ H 0 is the equilibrium melting enthalpy, which was 93.7 J/g for 100% crystalline PLA [ 22 ] and 287.30 J/g for 100% crystalline PE, [ 23 ] considering that only polyethylene sequences crystallize, and W is the matrix content.…”
Section: Methodsmentioning
confidence: 99%
“…where ΔH m is the melting enthalpy of PLA and EVA, ΔH 0 is the equilibrium melting enthalpy, which was 93.7 J/g for 100% crystalline PLA [22] and 287.30 J/g for 100% crystalline PE, [23] considering that only polyethylene sequences crystallize, and W is the matrix content. The melt fraction plots were acquired by integrating the DSC peaks using INTEGRAL software and Equations (3) and ( 4).…”
Section: Characterizationsmentioning
confidence: 99%
“…The PLA inherent brittleness usually requires additives to effectively produce blown films with acceptable properties. Although some authors reported that virgin PLA can only be successfully applied for rigid films applications, 12,13 a great deal of work has been done to improve processability and applications by adding plasticizers, 3,1418 chain extenders 17,19 and toughening agents, 1517,20,21 leading to improved mechanical, barrier and optical properties. Nevertheless, some melt strength enhancers, such as multifunctional epoxies and di-isocyanates, have not been approved for food applications, even if they are added at concentrations that are in compliance with regulations on compostability.…”
Section: Introductionmentioning
confidence: 99%